The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fonc.2020.00892
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Post-Mastectomy Radiotherapy for T1-2N1 Breast Cancers With Node-Positive Pathology After Patients Become Node-Negative Pathology Following Neoadjuvant Chemotherapy?

Abstract: Purpose: To assess the benefit of post-mastectomy radiotherapy (PMRT) in breast cancer (BC) patients with T1-2N1M0 who developed pathologically negative lymph nodes (ypN0) after undergoing neoadjuvant chemotherapy (NAC) and mastectomy. Patients and Materials: Patients with T1-2 tumors and positive lymph node(s) who became pN0 after NAC and mastectomy were screened from our prospectively maintained database. The primary endpoint was recurrence-free survival (RFS), and the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…The PubMed literature search resulted in 184 articles related to PMRT after NAC (from 1993 Mar to 2021 Nov), by using search terms "postmastectomy radiation therapy" "neoadjuvant chemotherapy" and "breast cancer" in all their forms. After reviewing the abstracts and full texts of all these literatures, nine studies [11][12][13][14][15][16][17][18][19] were found to report results comparable to our study. The summary of the literature search and a comparison of the nine studies to our results are presented in Table 6.…”
Section: Indications For Pmrt After Nac: Current Literature Reviewsupporting
confidence: 69%
See 1 more Smart Citation
“…The PubMed literature search resulted in 184 articles related to PMRT after NAC (from 1993 Mar to 2021 Nov), by using search terms "postmastectomy radiation therapy" "neoadjuvant chemotherapy" and "breast cancer" in all their forms. After reviewing the abstracts and full texts of all these literatures, nine studies [11][12][13][14][15][16][17][18][19] were found to report results comparable to our study. The summary of the literature search and a comparison of the nine studies to our results are presented in Table 6.…”
Section: Indications For Pmrt After Nac: Current Literature Reviewsupporting
confidence: 69%
“…The summary of the literature search and a comparison of the nine studies to our results are presented in Table 6. Five out of nine studies presented with OS analysis, within which three study [13,14,18] found that PMRT didn't improve OS in cN + who achieving ypN 0 after NAC, while another two [12,15] found that PMRT signi cantly improved OS in cN + patients after NAC, whatever achieving ypN 0 or still remaining ypN + patients. Besides the primary endpoint of OS, other endpoints (e.g.…”
Section: Indications For Pmrt After Nac: Current Literature Reviewmentioning
confidence: 99%
“…The initial search on PubMed yielded 1837 studies. After applying the inclusion and exclusion criteria, 13 studies were included in the meta-analysis [13] , [14] , [15] , [16] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A subgroup analysis was performed including three studies with data on the impact of LRRT on LRR in patients with pCR (both ypT0 and ypN0) [13] , [14] , [15] . In total, 390 patients were included in the analysis, 242 received LRRT and 148 did not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation